Import Substitution Policies: A Two-Sector, Fix-Price Model - Cuddington, John T. (Review of Economic Studies, 1981)
Journal Article Import Substitution Policies: A Two-Sector, Fix-Price Model Get access John T. Cuddington John T. Cuddington Stanford University Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 48, Issue 2, April 1981, Pages 327–342, https://doi.org/10.2307/2296889 Published: 01 April 1981 Article history Received: 01 November 1979 Accepted: 01 September 1980 Published: 01 April 1981